ENGLISH EDUCATION STUDENTS’ PERCEPTIONS OF WRITING THEIR FIRST RESEARCH PROPOSAL - Ika Yuli Wahyuni; Geminastiti Sakkir; Rini Isnaeni Sakkir (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study investigates English Education students’ perceptions of writing their first research proposal, focusing on the cognitive, linguistic, emotional, and instructional challenges they experience. A qualitative descriptive design was employed, involving twenty undergraduate students, ten third-semester students enrolled in the Academic Writing course, and ten fifth-semester students enrolled in Research Methodology. Data were collected through an open-ended Google Form questionnaire and were analyzed thematically following Braun and Clarke’s (2006) six-phase framework. Findings reveal six major themes: (1) limited prior knowledge and conceptual uncertainty, (2) difficulties understanding research components, (3) academic writing challenges, (4) emotional reactions including anxiety, low confidence, and overwhelm, (5) need for clearer guidance, examples, and support, and (6) expectations for improving proposal-writing instruction. Third-semester students commonly expressed confusion and unfamiliarity with basic research concepts, while fifth-semester students demonstrated greater theoretical understanding but still struggled to apply these concepts to actual writing tasks. Students also reported linguistic challenges such as organizing ideas, paraphrasing, using appropriate academic vocabulary, and applying APA formatting rules. Emotionally, students experienced anxiety and fear of making mistakes, which hindered their ability to engage confidently in the writing process. They consistently emphasized the need for step-by-step instruction, practical examples, writing workshops, and constructive feedback. Overall, this study highlights the importance of strengthening research literacy instruction in English Education programs by integrating conceptual understanding, academic writing support, process-based guidance, and emotional scaffolding. Enhancing these areas can help students develop the confidence and competence necessary to complete their research proposals effectively.